Message in Culture Nyaneut from Ethnic Sundanese Tradition - Agung Syaputra, Wawan Hernawan, Hasan Basri, (Opción, 2019)
The aim of the study is to investigate the message in culture Nyaneut from Ethnic Sundanese Tradition in the festival nyaneut via comparative qualitative research methods. The results showed that the culture nyaneutpeneitian initially as a habit in the SundaUrang drank together, accompanied by the traditional snack of boiled cassava and sugar in the area around Mount CikurayGarut. In conclusion, cultural messages contained in nyaneut traditions for that lies in the value increase and strengthen ties amongst individuals or citizens and a message to keep the natural kelesetarian mainly springs as a source of life together.